2014
DOI: 10.1111/jvs.12151
|View full text |Cite
|
Sign up to set email alerts
|

Refining rare weed trait syndromes along arable intensification gradients

Abstract: Question How does the conservation (rarity) value of arable weed communities differ along intensification gradients? Which functional traits best distinguish the weed communities of more and less extensively managed fields? Can the same traits predict the rarity of individual weed species? Location Hungary. Methods Using relevé data from 60 cereal and 70 stubble fields, together with weed trait data, we characterized community responses to arable intensification using functional trait analyses based on trait‐c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 44 publications
2
14
0
1
Order By: Relevance
“…Higher Ellenberg indices for nitrogen among arable weeds revealed their adaptation to the nutrient‐rich environment of arable fields resulting from fertilization. Plants with low nitrogen requirements are indeed rare in arable fields (Pinke and Gunton, ; Wagner et al., ) because agricultural intensification generally selects for nitrophilous plants (Fried et al., ; Storkey et al., ; Moreau et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher Ellenberg indices for nitrogen among arable weeds revealed their adaptation to the nutrient‐rich environment of arable fields resulting from fertilization. Plants with low nitrogen requirements are indeed rare in arable fields (Pinke and Gunton, ; Wagner et al., ) because agricultural intensification generally selects for nitrophilous plants (Fried et al., ; Storkey et al., ; Moreau et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In arable fields, early and long flowering can also be interpreted as a potential strategy to escape weed control and crop competition (Bagavathiannan and Norsworthy, ). Arable weeds with a short or late flowering period are indeed often rare in agroecosystems (Storkey et al., ; Pinke and Gunton, ).…”
Section: Discussionmentioning
confidence: 99%
“…Otte, Bissels, and Waldhardt (2006) found that the species which increased in arable habitats in recent decades tend to be characterized by relatively high temperature optima for germination. Similarly, Pinke and Gunton (2014) ascribe the rarity of late-winter and early-summer annuals to the fact that the timing of their emergence may make them more susceptible to early-season herbicide application, characteristic of intensive cereal farming.…”
Section: Causes Of the Decline Of Rare Speciesmentioning
confidence: 99%
“…These habitats generally have lower fertility than fertilized arable fields and are more likely to harbour legumes, a plant morphology which is predicted to increase under these conditions (van Elsen, ); in our study, legume species of the Coronilla , Medicago or Retama genera were found at higher frequency in landscapes with a larger proportion of semi‐natural habitat. The relative ecological stability of semi‐natural areas is also reflected in the presence of species with late time of first flowering (Pinke & Gunton, ) or autochory seed dispersal. Autochory is a short‐distance dispersal mechanism, and the low colonizing capacity over space suggests that species are in an optimal area.…”
Section: Discussionmentioning
confidence: 99%